2015
DOI: 10.1007/s12471-015-0659-8
|View full text |Cite
|
Sign up to set email alerts
|

Baseline NT-ProBNP level predicts success of cardioversion of atrial fibrillation with flecainide

Abstract: BackgroundPatients with acute-onset symptomatic atrial fibrillation (AF) can be treated with flecainide. However, flecainide may induce arrhythmias and/or exaggerate heart failure. Therefore, validated markers to predict the efficacy of flecainide and prevent adverse effects are required. We hypothesised that lower NT-proBNP plasma levels correlate with higher success rates of cardioversion with flecainide in patients with AF.MethodsIn this prospective single-centre study, we included 112 subsequent patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…NT-proBNP is a natriuretic hormone which, in the absence of heart failure, is secreted from the atrium in response to atrial distension and overload. [ 35 37 ] Consistent with the previous findings, [ 38 40 ] we showed that an increased plasma NT-proBNP level predicted a higher risk for AF recurrence post-PVI. Previous studies have demonstrated that BNP inhibited the resting sympathetic activity of the heart, thereby potentiating vagal activity through activating the cGMP pathway and inciting atrial overload and atrial remodeling, which results in sustaining atrial fibrillatory rotors and potentially initiating and sustaining AF.…”
Section: Discussionsupporting
confidence: 91%
“…NT-proBNP is a natriuretic hormone which, in the absence of heart failure, is secreted from the atrium in response to atrial distension and overload. [ 35 37 ] Consistent with the previous findings, [ 38 40 ] we showed that an increased plasma NT-proBNP level predicted a higher risk for AF recurrence post-PVI. Previous studies have demonstrated that BNP inhibited the resting sympathetic activity of the heart, thereby potentiating vagal activity through activating the cGMP pathway and inciting atrial overload and atrial remodeling, which results in sustaining atrial fibrillatory rotors and potentially initiating and sustaining AF.…”
Section: Discussionsupporting
confidence: 91%
“…In 17 of the 58 articles (29%), we noted discrepancies with AF guidelines, specifically regarding the PCV drug used, the patients' comorbidities and the PCV contraindications (Table 4). 16,18,[20][21][22][26][27][28]31,32,36,39,41,49,55,60,63 According to the data presented in the articles, it appeared that a total of 239 patients underwent PCV using a drug that was contraindicated given their specific comorbidities. In the described cases, the most common culprit PCV drug was ibutilide, followed by vernakalant, amiodarone, propafenone, and flecainide.…”
Section: Resultsmentioning
confidence: 99%
“…NT-pro BNP, a fractured fragment of BNP, is featured by long half-life period and easy detection compared to BNP. 11 Studies have found that NT-pro BNP has important significance in cerebrovascular diseases. 12 , 13 In this study, the level of NT-pro BNP of the observation group was significantly higher than that of the control group, which was consistent with the results of the current studies.…”
Section: Discussionmentioning
confidence: 99%